Dongshin Don Chang, Phinehas, the Sons of Zadok, and Melchizedek. Priestly Covenant in Late Second Temple Texts (LSTS 90; London – New York: Bloomsbury T&T Clark 2016) - Targoński, Mateusz Jan (The Biblical Annals, 2018)
Book review: Dongshin Don Chang, Phinehas, the Sons of Zadok, and Melchizedek. Priestly Covenant in Late Second Temple Texts (LSTS 90; London – New York: Bloomsbury T&T Clark 2016). Pp. XI+242. 114 (HB), 91.99 (eBook). ISBN 978-0-56766-704-5 (HB), 978-0-56766-705-2 (eBook) DOI: https://doi.org/10.31743/ba.2018.8.1.06